Optimalisasi peran pihak ketiga yang berkepentingan dalam praperadilan melalui penegakan hukum menuju pembaharuan hukum acara pidana - Panjaitan, Ananda Chrisna D. (Ex Aequo Et Bono Journal Of Law, 2024)
This article will explain the important role of third parties in pretrial institutions and analyze the legal standing of non-governmental organizations in reforming criminal procedural law. The additional interpretation made by the Constitutional Court Decision provides legal standing to the community represented by Non-Governmental Organizations as supervisors of possible errors or arbitrariness in terminating investigations or discontinuing prosecutions. Furthermore, in reforming the criminal procedure law, Commissioner Judges, who in the RKUHAP have duties and authority that have advantages compared to the Pretrial Institution in the KUHAP, are expected to also provide access to interested third parties, one of whose subjects is the public, to submit applications freely in accordance with the certain requirements.